659'Ikigai', subjective well-being and participation in community support activities among the elderly in Japan. (2nd September 2021) - Kamei, Midori; Motohashi, Chiemi; Inoue, Naoko; Nishina, Motoko; Ohta, Akiko; Miyazaki, Takashi; Takahashi, Mihoko; Uemura, Makiko
Abstract: : The Abstract Template is flexible to accommodate Empirical Results or Narrative style submission types. First, determine whether your presentation content fits within the Empirical Results style or Narrative style. Next, remove the section from the below template that does not fit your submission type and complete the appropriate section of the template accordingly. Please ensure that you follow the below format and instructions for your submission. Background: Text: 'Ikigai', subjective well-being which is the Japanese concept to a good life plays important role for a long and active aging. We examined the cross-sectional association between 'Ikigai' and participation in community support activities in the elderly aged 65-74 for building community social capital in the current active aging policy of Japan. Methods: Text: The target population was all residents aged 65-74 years without disabilities in a municipality, Japan. The self-administered questionnaires were mailed to 5, 163 individuals in 2018. A Total of 2, 283 persons responded (response rate, 44.2%). Participants provided information on basic characteristics, 'Ikigai', perceived health, and intention to participate in community support activities for the elderly, the children care, and the disabled. Results: Text: A total of 1, 089 (47.7%) persons showed positive intention to participate in community support activities for the elderly. Respondents who had 'Ikigai' were 1, 796 (78.7%). Respondents who had 'Ikigai' were more likely to participate in community support activities for the elderly than those who did not. The same trends were shown in community support activities for the children care or the disabled. Conclusions: Text: Elderly people who had 'Ikigai' were more likely to participate in community support activities. 'Ikigai' may have an important role for making mutual ties and good life for active aging in the community. Key messages: Text: 'Ikigai' may have an important role for active aging in the community.